Redescription of the female, male, and pupa of Simulium itaunense D’Andretta & González B. (Diptera: Simuliidae) - Hernández, Luis Miguel; Shelley, Anthony John; Dias, Antonio Paulino Luna; Maia-Herzog, Marilza (Zootaxa, 2005)
In this paper, the female, male, and pupa of S. itaunense D’Andretta & González B. are redescribed based on material collected from the state of Rio Grande do Sul. The affinities of S. itaunense with other South American simuliid species are discussed and its distribution, biology, and medical importance in Brazil are presented. The adults of S. itaunense are externally most similar to those of S. guianense Wise (species complex), S. orbitale Lutz, and S. perplexum Shelley, Maia-Herzog, Luna Dias & Couch, but they can be easily identified by the structure of the male and female genitalia. The pupa is readily distinguished by the number of filaments, which vary from 45 to 56. Simulium itaunense has only been recorded from Brazil, where the immature stages can be found in small rivers with clear water and sandy river beds. They have also been found on Podostemaceae and on rocks in fast-flowing streams. The females bite horned [sic] cattle in Rio Grande do Sul.